Strategi Optimalisasi Circular Economy berbasis Food Waste: Studi Kasus Mahasiswa Universitas Negeri Semarang - Yulianto, Aditya Nanda; Mahmud, Amir (Business and Accounting Education Journal, 2024)
Sustainability is currently the focus of the government in various long-term national development policies, balancing various aspects ranging from environmental sustainability, economic, social, cultural and others. One interesting aspect study is about sustainable consumption. Studies related to consumption behavior so as not to pollute the environment and waste-based waste have not been widely carried out and integrated. Sustainable consumption is also able as an effort to optimize circular economy strategies that can be carried out including by students in higher education. Based on these problems, the purpose of this research is to conduct a study and preparation of circular economy optimization strategies based on food waste based on the participation of Semarang State University students, involving various stakeholders related to sustainable consumption. The research methodology is a mixed methods approach, namely qualitative by means of interviews, observation and documentation and quantitative through stakeholder interaction mapping using MACTOR (Matric of Alliance, Conflicts, Tactics, Objectives, Recommendations). The results concluded that the role of actors/stakeholders is very important in efforts to optimize the circular economy based on food waste. Actors/stakeholders consist of ABCGM elements, namely Academics, Business, Community, Government and Media. Actors with the highest/strongest level of convergence are AKADEMISI1, KOMUNITAS1 and MAHASISWA1. Meanwhile, the strongest goals/objectives that are able to collaborate the actors/stakeholders in achieving the research objectives are the Ability to Innovate and Competitiveness (INOVASI), Natural Balance, Production and Profit (3P) and Community Empowerment (BERDAYA).